2010
DOI: 10.1002/hbm.21122
|View full text |Cite
|
Sign up to set email alerts
|

Regional gray matter density associated with emotional intelligence: Evidence from voxel‐based morphometry

Abstract: Emotional Intelligence (EI) is the ability to monitor one's own and others' emotions and the ability to use the gathered information to guide one's thinking and action. EI is thought to be important for social life making it a popular subject of research. However, despite the existence of previous functional imaging studies on EI, the relationship between regional gray matter morphology and EI has never been investigated. We used voxel-based morphometry (VBM) and a questionnaire (Emotional Intelligence Scale) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 83 publications
(80 reference statements)
12
127
1
1
Order By: Relevance
“…Mind pops were positively correlated with GMV in the right prefrontal gyrus and negatively correlated with GMV in the left temporal gyrus. The reverse tendency seems difficult to understand, leading to an open question to be answered for future studies (Takeuchi et al 2011;Banissy et al 2012). There are several factors unfolding such an observation.…”
Section: Discussionmentioning
confidence: 96%
“…Mind pops were positively correlated with GMV in the right prefrontal gyrus and negatively correlated with GMV in the left temporal gyrus. The reverse tendency seems difficult to understand, leading to an open question to be answered for future studies (Takeuchi et al 2011;Banissy et al 2012). There are several factors unfolding such an observation.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we used rGMD for two reasons. First, in our recent study, including subjects with the same characteristics as those of this study [Takeuchi et al, 2010a], rGMD across the brain was correlated with emotional intelligence, which represents the individual's emotional and social competence. Because this study addresses complex sexual behaviors in society, rGMD may be associated to a greater extent with sexual attitude.…”
Section: Preprocessing Of T1-weighted Structural Datamentioning
confidence: 87%
“…Seven hundred and seventy-seven healthy, right-handed individuals (433 men and 344 women; 20.7 6 1.9 years) participated in this study as part of an ongoing project investigating associations among brain imaging, cognitive functions, aging, genetics, and daily habits [Takeuchi et al, 2011a[Takeuchi et al, ,c, 2014a2013a, 2012a, 2010a,b, 2011cTaki et al, 2010Taki et al, , 2011. Data derived from the subjects in this study are to be used in other studies irrelevant to the theme of this study.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas those initial studies compared emotional/social-processing tasks to resting baseline, a subsequent study using a more complex auditory paradigm with a nonresting comparison condition found positive correlations between EI and some cortical emotional processing regions, while failing to find activation in more primitive regions such as the amygdala (Kreifelts, Ethofer, Huberle, Grodd, & Wildgruber, 2010). Recent structural neuroimaging studies have also suggested that measures of EI are related to gray matter volume within the vmPFC Koven, Roth, Garlinghouse, Flashman, & Saykin, 2011;Takeuchi et al, 2011), further supporting this region as a potentially important contributor to EI capacities.…”
Section: Questionnairesmentioning
confidence: 99%